Physiological Parameter Response to Variation of Mental Workload. (February 2018) - Marinescu, Adrian Cornelius; Sharples, Sarah; Ritchie, Alastair Campbell; Sánchez López, Tomas; McDowell, Michael; Morvan, Hervé P.
Objective: To examine the relationship between experienced mental workload and physiological response by noninvasive monitoring of physiological parameters. Background: Previous studies have examined how individual physiological measures respond to changes in mental demand and subjective reports of workload. This study explores the response of multiple physiological parameters and quantifies their added value when estimating the level of demand. Method: The study presented was conducted in laboratory conditions and required participants to perform a visual-motor task that imposed varying levels of demand. The data collected consisted of physiological measurements (heart interbeat intervals, breathing rate, pupil diameter, facial thermography), subjective ratings of workload (Instantaneous Self-Assessment Workload Scale [ISA] and NASA-Task Load Index), and the performance. Results: Facial thermography and pupil diameter were demonstrated to be good candidates for noninvasive workload measurements: For seven out of 10 participants, pupil diameter showed a strong correlation ( R values between .61 and .79 at a significance value of .01) with mean ISA normalized values. Facial thermography measures added on average 47.7% to the amount of variability in task performance explained by a regression model. As with the ISA ratings, the relationship between the physiological measures and performance showed strong interparticipant differences, with some individuals demonstrating a much stronger relationship between workload and performance measures than others. Conclusion: The results presented in this paper demonstrate that physiological and pupil diameter can be used for noninvasive real-time measurement of workload. Application: The methods presented in this article, with current technological capabilities, are better suited for workplaces where the person is seated, offering the possibility of being applied to pilots and air traffic controllers.